Direct Printing of Micropatterned Plasmonic Substrates of Size‐Controlled Gold Nanoparticles by Precision Photoreduction (Advanced Optical Materials 1/2021). Issue 1 (4th January 2021) - Zhang, Yangxi; Liang, Zengtian; Zhang, A. Ping; Tam, Hwa‐Yaw
Abstract : A precision photoreduction technology for direct printing of the micropatterns of size‐controlled gold nanoparticles (AuNPs) is presented by A. Ping Zhang and co‐workers in article number 2001368 . A digital ultraviolet light processing technique is applied to precisely control the growth of AuNPs via dynamic optical patterns to create micrometer‐scale micropatterns of AuNPs with a target size on the titanium dioxide nanolayer‐capped quartz substrate. This printing technology offers new opportunities to rapidly fabricate various kinds of miniature plasmonic devices ranging from plasmonic sensors to plasmonically enhanced light–matter interaction applications.